The stock optimization of automated warehouse - Fedun, R. S.; Litvinov, A. L. (НТУ ДП, 2021)
Automated warehouses play an important role in the functioning of production. One of the tasks of managing the warehouse system is to select the optimal size of the stock that is stored in the warehouse. In real production systems, certain delays are possible and common in the arrival of the next batch of goods of volume Q. Therefore, in the general case, the process of their receipt is random. One can compensate the deviations from the delivery schedule by introducing a safety stock of qstr, which allows organizing of the stable operation of the entire system.
Keywords: оптимізація; складська система; научная публикация НГУ 2021